Effectiveness of preformed physical factors in the correction of dry eye syndrome after phacoemulsification: a randomized trial - Marina K. Shulikova; Irina P. Shurygina (Вестник восстановительной медицины)
Introduction. Currently, modern high-tech methods of small incision cataract surgery are not always immune to the development of iatrogenic «dry eye» syndrome. Currently, one of the common complications of the anterior segment of the eye after small incision cataract surgery is the development of iatrogenic dry eye syndrome, which leads to a decrease in the quality of medical and social rehabilitation of operated patients.